The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.